The Functional Construction of Advertisements in the Iraqi Press Websites - جمعة الربيعي بيرق حسين (ALBAHITH ALALAMI, 2015)
Communication and media technologies have seen several changes in the last two decades. These changes put the basis for the emergence of communicative and media practices on several levels including political, economic, technological and artistic. And these, in turn, led to the emergence of new media trends and phenomena in various areas of media worthily to be studied and researched for example online advertisings. Online advertising is a marketing process for which several features are Communication and media technologies have seen several changes in the last two decades. These changes put the basis for the emergence of communicative and media practices on several levels including political, economic, technological and artistic. And these, in turn, led to the emergence of new media trends and phenomena in various areas of media worthily to be studied and researched for example online advertisings. Online advertising is a marketing process for which several features are provided by the internet. The designers and directors of advertisings are able to design elements employed in designing online advertisings. Advertising is an effective visual element in the construction of the pages and websites. The research sample includes al-sabah aljadid newspaper, al-Sumaria news, and anbaa Almada agency. The visual images provided by the announcements stand our through simulating the browsers’ fantasies about the constituent elements of the online advertisings and this can be done by virtue of interactive technologies (two- or three-dimensional image) and employing color stimuli and sound and visual effects which serve as an attractive tool about the content of the advertising message. So, the research is done to know the nature of the use of advertising of the sample websites positively or negatively in terms of identifying the foundations and technical and functional processes of the research sample by dividing the material into The results of the research show that the research sample stretches dramatically the extensions of the first page in which advertisings are published and they are concerned with employing effective advertising